Drug-related problems and changes in drug utilization after medication reviews in nursing homes in Oslo, Norway - Amura Francesca Fog; Gunnar Kvalvaag; Knut Engedal; Jørund Straand (Taylor & Francis Group, 2017)
Objective: We describe the drug-related problems (DRPs) identified during medication reviews (MRs) and the changes in drug utilization after MRs at nursing homes in Oslo, Norway. We explored predictors for the observed changes. Design: Observational before-after study. Setting: Forty-one nursing homes. Intervention: MRs performed by multidisciplinary teams during November 2011 to February 2014. Subjects: In all, 2465 long-term care patients. Main outcome measures: DRPs identified by explicit criteria (STOPP/START and NORGEP) and drug-drug interaction database; interventions to resolve DRPs; drug use changes after MR. Results: A total of 6158 DRPs were identified, an average of 2.6 DRPs/patient, 2.0 for regular and 0.6 for pro re nata (prn) drugs. Of these patients, 17.3% had no DRPs. The remaining 82.7% of the patients had on average 3.0 DRPs/patient. Use of unnecessary drugs (43.5%), excess dosing (12.5%) and lack of monitoring of the drug use (11%) were the most frequent DRPs. Opioids and psychotropic drugs were involved in 34.4% of all DRPs. The mean number of drugs decreased after the MR from 6.8 to 6.3 for regular drugs and from 3.0 to 2.6 for prn drugs. Patients with DRPs experienced a decrease of 1.1 drugs after MR (0.5 for regular and 0.6 for prn drugs). The reduction was most pronounced for the regular use of antipsychotics, antidepressants, hypnotics/sedatives, diuretics, antithrombotic agents, antacid drugs; and for prn use of anxiolytics, opioids, hypnotics/sedatives, metoclopramide and NSAIDs. Conclusion: The medication review resulted in less drug use, especially opioids and psychotropic drugs.